Investigando relações ecológicas sob a perspectiva de valorização dos parques urbanos - Dayane Stefany da Rocha Silva (2022)
The present work aimed to develop a didactic sequence with an investigative approach on ecological interactions, using the Gentil Diniz Municipal Park, Contagem (MG) as an non-formal education space, thus rescuing the importance of environments like this for the conservation of biodiversity and well-being. human. As final products developed and made available for the use of third parties, were produced: a) a didactic sequence, b) an image guide with records made in the park, which highlight the ecological interactions observed in the place and c) a digital booklet with the recorded interactions. In order to verify the use of the space by the local residents and their evaluation of what the space offers, a questionnaire was applied to 23 residents of the surroundings of the park. For these residents, living near an urban park has the benefits of improving the quality of life, air, and the physical and mental health of visitors. Considering a total area of 24,000 m² and nine hours of work, 34 ecological interactions were observed and recorded, such as: mutualism, inquilinism, society, pollination, herbivory and zoochory. The park is an environment conducive to carrying out investigative activities, due to its environmental, historical and cultural wealth.